2023
DOI: 10.3390/ijms25010369
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Alleviates Oxidative Stress in Chronic Obstructive Pulmonary Disease Induced by Cigarette Smoke via Modulation of the TRPV1 and CYP2A13/NRF2 Signaling Pathways

Lina Zhou,
Tunyu Jian,
Yan Wan
et al.

Abstract: The current study aims to investigate the therapeutic potential of luteolin (Lut), a naturally occurring flavonoid found in various medicinal plants, for treating chronic obstructive pulmonary disease (COPD) through both in vitro and in vivo studies. The results demonstrated that Lut increased body weight, reduced lung tissue swelling and lung damage indices, mitigated systemic oxidative stress levels, and decreased alveolar fusion in cigarette smoke (CS)- and lipopolysaccharide (LPS)-induced COPD mice. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“… 20 When cigarette smoke is inhaled into the lungs, it first causes oxidative stress and inflammation in the lungs, activates the inflammatory signaling pathway of airway epithelial cells and alveolar macrophages, recruits more immune cells to the lungs, secretes a large number of inflammatory factors and proteases and then further amplifies inflammation, accompanied by imbalance between oxidative stress and proteinase-antiprotease. 21 Besides, cigarette smoke has been elucidated to be a predominant source of ROS, and excessive ROS production contributes to oxidative stress, thereby triggering the development of pathological changes in the lungs of COPD patients 22 In addition, CSE can activate molecules involved in the cell cycle and mediate cell apoptosis. 23 Moreover, the abnormal inflammation in the lungs caused by the inhalation of cigarette smoke has close association with COPD.…”
Section: Discussionmentioning
confidence: 99%
“… 20 When cigarette smoke is inhaled into the lungs, it first causes oxidative stress and inflammation in the lungs, activates the inflammatory signaling pathway of airway epithelial cells and alveolar macrophages, recruits more immune cells to the lungs, secretes a large number of inflammatory factors and proteases and then further amplifies inflammation, accompanied by imbalance between oxidative stress and proteinase-antiprotease. 21 Besides, cigarette smoke has been elucidated to be a predominant source of ROS, and excessive ROS production contributes to oxidative stress, thereby triggering the development of pathological changes in the lungs of COPD patients 22 In addition, CSE can activate molecules involved in the cell cycle and mediate cell apoptosis. 23 Moreover, the abnormal inflammation in the lungs caused by the inhalation of cigarette smoke has close association with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired Nrf-2 has been shown to contribute potentially to the development of COPD [ 41 ]; this could be due to the Nrf-2 pathway's role in increasing antioxidant defense and decreasing lung inflammation and alveolar apoptosis. These mechanisms help protect alveolar cells from the harmful effects of tobacco smoke [ [42] , [43] , [44] ]. At the same time, recent studies have also shown that activation of the Nrf-2 pathway can balance redox reactions in COPD and restore macrophage function, thus playing a protective role [ 45 ].…”
Section: Introduction To Nrf-2 and Its Role In Disease Modelsmentioning
confidence: 99%